Patient accrual and understanding of informed consent in a two-stage consent design. (June 2021) - Vickers, Andrew J; Vertosick, Emily A; Carlsson, Sigrid V; Ehdaie, Behfar; Kim, Scott Y H
Background: We previously introduced the concept of "two-stage" (or "just-in-time") informed consent for randomized trials with usual care control. We argued that conducting consent in two stages—splitting information about research procedures from information about the experimental intervention—would reduce the decisional anxiety, confusion, and information overload commonly associated with informed consent. We implemented two-stage consent in a low-stakes randomized trial of a mindfulness meditation intervention for procedural distress in patients undergoing prostate biopsy. Here, we report accrual rates and patient understanding of the consent process. Methods: Patients approached for consent for the biopsy trial were asked to complete the standard "Quality of Informed Consent" questionnaire to assess their knowledge and understanding of the trial. Results: Accrual was excellent with 108 of 110 (98%) patients approached for consent signing first-stage consent. All 51 patients randomized to the experimental arm and who later presented for biopsy signed second-stage consent and received the mindfulness intervention. Quality of Informed Consent data were available for 48 patients assigned to the mindfulness treatment arm and 44 controls. The mean Quality of Informed Consent score was similar in the meditation and control arms with and overall mean of 75 (95% confidence interval = 74–76) for the knowledge section and 86 (95% confidence interval = 81–90) for understanding, comparable to the normative scores of 80 and 88. On further analysis and patient interview, two of the Quality of Informed Consent questions were found to be misleading in the context of a two-stage consent study for a mindfulness intervention. Excluding these questions increased knowledge scores to 88 (95% confidence interval = 87–90). Conclusion: We found promising data that two-stage consent facilitated accrual without compromising patient understanding of randomized trials or compliance with allocated treatment. Further research is needed incorporating randomized comparison of two-stage consent to standard consent approaches, measuring patient anxiety and distress as an outcome, using suitable modifications to the Quality of Informed Consent questionnaire and trials with higher stakes.